Perception and self-reported practice on clinical practice guidelines among family physicians comparison between participants and non-participants of post-graduate course on clinical practice guidelines of the Department of Family and Community Medicine, College of Medicine, Philippine General Hospital, University of the Philippines Manila - Ali, Balgis
Objective: To compare the perception and self-reported practice or utility of clinical practice guidelines (CPG) among family physicians who attended a postgraduate course on CPG and family physicians who did not attend a postgraduate Course on CPG. Design: A cross-sectional comparative study design was employed to quantify the differences in the perception toward and practice by family physicians of clinical practice guidelines among those who attended a postgraduate course on clinical practice guidelines as compared with those who did not. Setting: The study was done in Metro Manila, Philippines. Subjects: A total of 120 Family Physicians from Metro Manila, sixty family physicians who attended a Postgraduate course on CPG conducted by Department of Family and Community Medicine, UP-PGH, the participants group, and sixty family physicians who did not attend a Postgraduate course on CPG, to the non-participants groups were included in the study. Main Outcome Measures and Data Analysis: Perception and utilization of clinical practice guidelines were obtained from ?Perception and Self-reported Practice on Clinical Practice Guidelines Questionnaires. The two-tailed t-test was used to compare mean scores of participants and non-participants. To compare the differences of the responses between two groups, the chi-square test for nominal data and a two-tailed Fisher?s exact test were used. Logistic regression was likewise used to determine the risk factors for positive perception regarding CPG. The level of significance was set at 0.05 for all tests. Results: The majority of participants and non-participants felt that CPG was a good tool for education and improved patient care. Participants of the postgraduate course had a more positive perception than non-participants toward CPG. This was proven by data on a more positive perception held by participants in twenty (20) questions, seven (7) of which were statistically significant. One hundred percent of the participants and majority (88.3%) of the non-participants reported that they used CPG in their practice, this difference being deemed statistically significant. All of the participants and majority (96.7%) of non-participants had greater confidence in CPG issued by their respective organizations. One hundred percents of participants and 90% of non-participants preferred a postgraduate course or continuing medical education as the best method for disseminating CPG. Conclusions: Results showed that the Postgraduate course was an effective method in the dissemination of clinical practice guidelines. The effectiveness of the postgraduate course in influencing perception and practice, supports the finding that a postgraduate course be continued as the best, if not one of the main strategies for disseminating CPG. Supports the finding that a postgraduate course be continued one of the main strategies for disseminating CPG.